Children's perspectives on the benefits and burdens of research participation. Issue 1 (2nd January 2018) - Barned, Claudia; Dobson, Jennifer; Stintzi, Alain; Mack, David; O'Doherty, Kieran C.
ABSTRACT: Background : Participation in research is associated with benefits and burdens for individual research participants. Children living with a chronic illness are considered particularly vulnerable as they are already burdened with symptoms of their illness. In particular contexts, such as learning health care systems (LHS), where research and clinical care are integrated, children with chronic illnesses may be asked to participate in research related to their illness. A growing body of literature has focused on children's perspectives as research subjects; however, a relatively understudied aspect concerns children's experiences of research in clinics where they are also patients.Methods : We interviewed 25 Canadian children and adolescents living with inflammatory bowel disease (IBD) about their experiences of research participation.Results : Our participants described aspects of the research process and particular experiences as benefits and others as burdens. Benefits included helping others, receiving incentives, receiving the results of previous studies, and participating in fun activities. Burdens included the time required for particular types of research, physical and psychological discomfort, and feelings of obligation.Conclusions : Our study describes the experiences of children participating in research at a site that integrates research and clinical care. Our participants described experiences that often go unreported (such as feelings of obligation); we mention these as important considerations to be mindful of when interacting with children as (potential) research participants in an LHS and when thinking about research ethics protocols or the assent/consent process.